ANALISIS KELAYAKAN BUDIDAYA IKAN GURAME DI DESA KEDUNG REJO BUAY MADANG TIMUR KABUPATEN OKU TIMUR - Yudi Zuriah (Jurnal Bakti Agribisnis, 2016)
The objectives of this research are: (1) To calculate the cost, income and income earned by farmers in gouramy cultivation in every production process, (2) To analyze the feasibility of gouramy culture in Kedung Rejo Village Buay Madang Timur OKU Timur. This research was conducted in Kedung Rejo Village, Buay Madang Timur Sub-district, East OKU Regency. Selection of places chosen purposively with the consideration that the village of Kedung Rejo including the village that some farmers there who cultivate gourami. The study was conducted in February 2014. The study found that the total production cost incurred in gouramy fish culture amounted to Rp 19,316,827.00 per process, receipt during one production process of Rp 35,020,333.00, so the income received was Amounting to Rp 15.703.507,00 per process. The R / C ratio is 1.77 indicating the profitability of the carp cultivation and the value of NPV is Rp 20,871,523, the IRR value is 42% and the value of Net B / C is 1.79 which shows the cultivation of a proper gouramy (Feasible) to be developed.